Efetividade da doxiciclina na profilaxia contra letptospirose - Monteiro, Glória Regina de Goes (2003)
Leptospirosis is a worldwide zoonosis of considerable medical and economical importance that affects humans in both urban and rural contexts, as well as domestic animals and wild fauna. Leptospira interrogans is the causative agent and is transmitted to humans by indirect contact with contaminated soil or water. The clinical syndromes include sub clinical infection, self-limited anicteric febrile illness, and severe and potentially fatal illness, known as Weil´s syndrome. In developed countries, leptospirosis is related to occupational or recreational activities while in developing countries, outbreaks occur during floods. In those regions, traditional strategies to prevent the transmission are difficulties to be implemented because of costs and lack of community acceptance. In addition, no efficient vaccine is available for human use. Several studies have suggested that chemoprophylaxis with doxycycline pre and post-exposure may be effective to prevent leptospirosis. Leptospirosis has been reported in rural areas of the State of Rio Grande do Norte, Brazil since 1985 in rice farmers who present the anicteric illness. The disease cause great social and economics impact. The study was conducted in São Miguel where an epidemic of leptospirosis in rice farmers was reported. The main objective was to determine the efficacy of doxycycline in preventing Leptospira exposure. A taxa de soroprevalência de leptospirose na população estudada antes e após a colheita foi de 14,2% (n=22) e de 16.6% (n=27) respectivamente. Anti-Leptospira serology was determined for 61 subjects in two instances, pre and post-exposure to potential contaminated water. There was an increased risk of 29.0 per cent in acquiring infection for individuals that did not use doxycycline. In addition, an increased risk of 30.0 % observed in farmers who did not use protection when exposed to Leptospira. The adhesion to preventive chemoprophylaxis was 55.7%. Therefore doxycycline, under specific circunstances appears to be an effective alternative to protect against leptosprirosis infection. A large sample composed of individuals to adhere to preventive therapy is needed to define time, dosage and length of use of doxycycline in this area